Amnion as a prosthetic material in congenital defects - Zachariou, Zacharias; Daum, Roland (Pediatric surgery international, 1996)
In pediatric surgery, amniotic membranes taken from autologous placenta are occasionally used as an implant in cases of large ventral abdominal clefts. The questions arise, which part of this organ should be used and how to use it in the recipient organism. Amniotic membranes consist anatomically of amnion and chorion, which are of fetal origin, and maternal decidua. In our experimental studies, we used the fetal parts of the amniotic membrane as an implant in a standardized rat model and investigated the utilization and possible foreign-body reaction (FBR) induced. Fifteen, 30, and 90 days after implantation the macroscopic appearance, light microscopy, and immunohistology of the specimens were examined. Adhesions to parenchymal organs and omentum were present irrespective of the side facing the abdominal cavity. Amnion induced a rapid FBR that diminished with time. Chorion and parts of the amnion were resorbed within the examined period after infiltration with recipient cells and neovascularization. Our studies have shown that for best results, only amnion in its anatomical definition and parts of the chorion should be prefered as an implant.
Elektronische Reproduktion der Druck-Ausgabe 21. September 2013
Gesehen am 09.09.2024